Marketing Strategy Analysis to Develop Business Using SWOT Analysis Method - Aulia, Niki; Imsar, Imsar; Dharma, Budi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Rich Mango Thai is an MSME engaged in the culinary business by selling processed mango juice and other fruit. The location of this business is very close to other beverage businesses, so the owner must have the right marketing strategy in order to win the market. Since its establishment in May 2022, Rich Mango Thai has been selling products that are very popular with the public. However, based on the sales data obtained, sales from May 2022 to April 2023 tend to decline. This research aims to understand the marketing strategy used by Rich Mango Thai in developing a business. This type of research uses a qualitative descriptive methodology. Primary and secondary data are the types and sources used, and interviews and observations are used as data collection methodologies. A descriptive analysis of the data is used, and the idea of ​​the 4P Marketing Mix (Product, Price, Place, Promotion) is mentioned. The researchers also conduct a SWOT analysis in assessing alternative strategies that can be implemented. SWOT analysis is also useful for finding out the strengths, weaknesses, opportunities, and threats possessed by Rich Mango Thai. The researchers also describe an analysis of Sharia marketing based on 3 paradigms namely Sharia Marketing Strategy to win Mind Share, Sharia Marketing Tactic to win Market Share, and Sharia Marketing Value to win Heart Share. In the final analysis, Rich Mango Thai is in quadrant I and has the main alternative strategy, namely the SO strategy, besides that Rich Mango Thai fulfills the character and paradigm of Sharia marketing.